ABA‐inducible DEEPER ROOTING1 improves adaptation of maize to water deficiency. Issue 11 (22nd July 2022) - Feng, Xuanjun; Jia, Li; Cai, Yunting; Guan, Huarui; Zheng, Dan; Zhang, Weixiao; Xiong, Hao; Zhou, Hanmei; Wen, Ying; Hu, Yue; Zhang, Xuemei; Wang, Qingjun; et al.
Summary: Root architecture remodelling is critical for forage moisture in water‐limited soil. DEEPER ROOTING 1 ( DRO1 ) in Oryza, Arabidopsis, and Prunus has been reported to improve drought avoidance by promoting roots to grow downward and acquire water from deeper soil. In the present study, we found that ZmDRO1 responded more strongly to abscisic acid (ABA)/drought induction in Zea mays ssp . mexicana, an ancestral species of cultivated maize, than in B73. It was proposed that this is one of the reasons why Zea mays ssp . mexicana has a more noticeable change in the downward direction angle of the root and fewer biomass penalties under water‐deficient conditions. Thus, a robust, synthetic ABA/drought‐inducible promoter was used to control the expression of ZmDRO1 B73 in Arabidopsis and cultivated maize for drought‐resistant breeding. Interestingly, ABA‐inducible ZmDRO1 promoted a larger downward root angle and improved grain yield by more than 40% under water‐limited conditions. Collectively, these results revealed that different responses to ABA/drought induction of ZmDRO1 confer different drought avoidance abilities, and we demonstrated the application of ZmDRO1 via an ABA‐inducible strategy to alter the root architecture of modern maize to improve drought adaptation in the field.